2018
DOI: 10.1002/pssr.201800396
|View full text |Cite
|
Sign up to set email alerts
|

Possible Origin of the Absence of Magnetic Order in LiOsO3: Spin–Orbit Coupling Controlled Ground State

Abstract: LiOsO 3 is the first experimentally confirmed polar metal with ferroelectric-like distortion. One puzzling experimental fact is its paramagnetic state down to very low temperature with negligible magnetic moment, which is anomalous considering its 5d 3 electron configuration since other osmium oxides (e.g., NaOsO 3 ) with 5d 3 Os ions are magnetic. Here the magnetic and electronic properties of LiOsO 3 are re-investigated carefully using the first-principles density functional theory. The calculations reveal t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Previous works based on both local density approximation (LDA) + U and LDA + dynamic meaning field theory (DMFT) both suggested that the ground state of LiOsO3 is just located near the critical point of metal-insulator transition [10]. If the Coulomb repulsion of Os 5+ is weak enough, the strong hybridization between Os's 5d and O's 2p orbitals and spin-orbit coupling (SOC) will suppress the local magnetic moment in LiOsO3 completely and then the ground state should be metallic.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous works based on both local density approximation (LDA) + U and LDA + dynamic meaning field theory (DMFT) both suggested that the ground state of LiOsO3 is just located near the critical point of metal-insulator transition [10]. If the Coulomb repulsion of Os 5+ is weak enough, the strong hybridization between Os's 5d and O's 2p orbitals and spin-orbit coupling (SOC) will suppress the local magnetic moment in LiOsO3 completely and then the ground state should be metallic.…”
Section: Introductionmentioning
confidence: 99%
“…The Coulomb repulsion in correlated electron systems is usually characterized by the on‐site Hubbard U . As the Coulomb repulsion should be insignificant in 5d systems because of the spatially extended 5d orbitals, we have carefully investigated the ground state of LiOsO 3 by performing two different types of DFT + U methods: the LDA + U method introduced by Liechtenstein et al in which the exchange splitting J and the Hubbard U are considered separately and the simplified local spin density approximate (LSDA) + U method introduced by Dudarev et al which only needs a parameter U eff = U − J . In the LDA + U case, the suitable value of Hubbard U in LiOsO 3 should be in the range of 1.0–2.0 eV, but in LSDA + U case, the value of U eff should be small enough (≈0 eV), i.e., a bare LSDA calculation is a proper choice.…”
mentioning
confidence: 99%
See 3 more Smart Citations